A Practical Demonstration of Social Networking System in a University Setting: A Case Study of Obong University (Global Journal of Human-Social Science, 2019)
The study has to do with the explorations of a way to use the internet services to provide a platform for theuse of individuals groups of people and companies to interact with one another through the social media The social media has really assisted interaction and even bringing together business tycoons and their services together through social networking forums blogs etc
Keywords: internet services; social media; social networking; networking system forums